Antifungal amide from leaves of Piper hispidum - Alecio, A. C.; Bolzani, Vanderlan da Silva [UNESP]; Young, MCM; Kato, M. J.; Furlan, Maysa [UNESP] (Amer Chemical Soc, 1998)
Bioactivity-guided fractionation of a CH2Cl2 extract from leaves of Piper hispidum (Piperaceae) yielded a new pyrrolidine amide, N-[7-(3',4'-methylenedioxyphenyl)-2(Z),4(Z)-heptadienoyl] pyrrolidine 1, in addition to two known amides N-[5-(3',4'-methylenedioxyphenyl)-2(E)-pentadienoyl]pyrrolidine and N-[2-(3',4'-methylenedioxy-6'-methoxyphenyl)-2(Z)-propenoyl]pyrrolidine. The structure of compound 1 was elucidated by interpretation of spectral data, including ES-MS. Compound 1 showed antifungal activity against Cladosporium sphaerospermum.